Oxidant/anti-oxidant imbalances in patients with long bone fractures - White, Hayden Thomas Wesley (My University, 2014)
The occurrence o f fat embolisation following trauma is a well recognised clinical entity and may occur in up to 90% of patients with long bone fractures. However, the fat embolism syndrome (FES) which consists of hypoxia, acute lung injury, central nervous system depression, and axillary or subconjunctival petechiae is only noted in 0.5-3% of these patients. Various theories have been put forward to explain the syndrome but none have thus far been able to explain this discrepancy. OBJECTIVES Our aim was to show that there is stimulation of the inflammatory system in patients with long bone fractures resulting in the production of lipid peroxides, and that an imbalance between the pro and antiinflammatory mediators may be responsible for the hypoxia observed in most patients. METHODS Nineteen people with long bone fractures of the lower limbs were followed for 48 hours. Blood specimens were taken for arterial blood gas (ABG), lipid peroxides (LPO), vitamin C, glutathione, C-reactive protein (CRP), full blood count (FBC) at time of admission and 12, 24 and 48 hours after admission. RESULTS There was evidence of lung involvement with an increase in the alveolar/arterial difference (A-aD02) from a mean of 13.8 mmHg to 23.3mmHg. Thirteen out of 16 patients (who had accurate ABG’s) showed an increased A-aD02. The white cell count (WCC) was raised initially with a mean of 13.8 x 109A. Within 48 hours, there had been a decrease to 8.9 x 109/1 (p=0.003). In keeping with an inflammatory response, there was a significant rise in the CRP in the 48 hours period from a mean of 9.7pg/l to 127.3pg/l (pO.OOOl) and a decrease in the platelet count from a mean of 256 x 109/1 to 193 x 109/1 (p=O.OOOJ} Furthermore, there was an increase in the lipid peroxides from 3.79nmol/ml to 5.81nmol/ml (p=0.03) over the first 24 hours ami to 6.42nmol/ml (p=0.20) over the 48 hour period. The anti-oxidants vitamin C and glutathione showed a decrease, vitamin C from 8.26jjg/ml to 7.45p,g/ml (p=0.05) and glutathione from 5.96pmol/ml to 3.84jimol/ml (p=0.22). Only one of the patients developed the fat embolism syndrome suggested by contusion, hypoxia, and upper body petechiae. CONCLUSION Patients with fractured long bones appear to have stimulation of their inflammatory system. There is evidence of activation of the coagulation system in keeping with this process. Serum antioxidants maintain homeostasis and may be responsible for the prevention of the FES in most patients. However, even in asymptomatic individuals, there is evidence of pulmonary involvement. One explanation for the development of FES in patients with long bone fractures is an imbalance between the pro and anti-inflammatory mediators with the production of lipid peroxides leading to organ dysfunction such as ARDS.